2000
DOI: 10.1001/jama.283.24.3205
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA Reductase Inhibitors and the Risk of Fractures

Abstract: This study suggests that current exposure to statins is associated with a decreased risk of bone fractures in individuals age 50 years and older. This finding has a potentially important public health impact and should be confirmed further in controlled prospective trials. JAMA. 2000;283:3205-3210

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
1
8

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 412 publications
(186 citation statements)
references
References 22 publications
(15 reference statements)
4
173
1
8
Order By: Relevance
“…Some observational studies have also found an association between increased BMD and statin use [3,4]. In addition, other cross-sectional or retrospective case-control studies have indicated that statins may protect against fractures [5][6][7][8]. Prospective population-based cohort studies concerning effects of HMG-CoA reductase inhibitors on BMD change have not been published.…”
Section: Introductionmentioning
confidence: 99%
“…Some observational studies have also found an association between increased BMD and statin use [3,4]. In addition, other cross-sectional or retrospective case-control studies have indicated that statins may protect against fractures [5][6][7][8]. Prospective population-based cohort studies concerning effects of HMG-CoA reductase inhibitors on BMD change have not been published.…”
Section: Introductionmentioning
confidence: 99%
“…Statins have recently been shown to reduce osteoclast activity and to stimulate osteoblast differentiation in vitro and bone formation in vivo (2)(3)(4). The role of statins in increasing bone mineral density in experimental animals and their role in protecting against fractures in cross-sectional or retrospective case control studies have led to testing this group of drugs for osteoporosis management (3,(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Interestingly, a protective effect for fractures of the hip, vertebral body, and foot in individuals aged 50 years and older after relatively short treatment periods was reported. This protective effect was much weaker or not present when other lipid-lowering drugs were used [154]. In a first case report about the treatment of a young woman with type I osteogenesis imperfecta with 0.8 mg cerivastatin per day for 6 months, bone-forming effects were reflected in an sharp increase in specific bone-formation markers after starting the treatment.…”
Section: Effect Of Cerivastatin On Bone Formationmentioning
confidence: 99%